Thermal Detection of Water Saturation Spots For Landslide Prediction - Aufa, Zin; Kamarul Hawari, Ghazali; Norliana, Khamisan (Asian Research Publishing Network (ARPN), 2015)
Nowadays, we heard many serious issues about landslide phenomenon in Malaysia. It became serious when landslide phenomenon affects human’s life. It causes human injury, loss of life and economical problem. There are a few factors that caused landslide but the main factor is heavy rain. Hence, to solve this issue, this study investigates a new method to detect spots of high water saturation which is integrated with a thermal camera system to provide early detection of landslide. The thermal camera is selected because it provides accurate predict where landslide going to occur. Thermal camera can be used to detect spots of high water saturation which is a key component that contributes to landslide activity. The technique of neural network is used to classify the image of water saturation. The analysis is done using 40 samples. It was tested to classify the data into two groups which are low water saturation and high water saturation